Phenytoin induced Lyell’s syndrome: a case report - Sivasamy, Manoj; R., Shreenidhi; M. K., Nishaanth; M., Jagadeesan; S., Prasanna Karthik (International Journal of Advances in Medicine, 2022)
Lyell’s syndrome commonly known as Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) is a type of severe allergic reactions affecting the skin and mucous membranes. If surface area of the body (BSA) involvement is less than 10% which is called as SJS and TEN is defined as epidermal detachment >30% of the total body surface area while both SJS and TEN can have involvement of mucosa. BSA with 10–30%, there is overlapping of SJS and TEN. We report a rare, life-threatening case of Lyell’s syndrome who presented lesions involving 30% of BSA after the oral intake of phenytoin and she was successfully treated with high-dose steroids and supportive care.